THE IMPORTANCE OF THE CHANGING DEMOGRAPHIC PROFILE ON THE SUCCESS OF POST GRADUATE ACCOUNTING STUDENTS - Ungerer, M.; Becker, A.I.; Nieuwoudt, M.J.; Swart, O.; Wilcocks, J.S. (South African Journal of Higher Education, 2016)
A study was undertaken to determine which variables in the demographic profile of students at the University of South Africa (UNISA) influence academic performance in their first attempt at obtaining the Certificate in the Theory of Accountancy. An inferential research study on secondary data was performed to determine which of certain predictor variables, of the demographic profile, namely ‘age group’, ‘assessment language’, ‘previous institution’, ‘race’, ‘gender’ and ‘occupation’, can influence academic performance. ‘Gender’ and ‘occupation’, not having a statistically significant relationship with the outcome variable, were excluded from the multivariable analysis performed. The findings revealed that students younger than 25 years of age, who are assessed in their home language and complete their undergraduate studies at an institution other than the University of South Africa, have a greater chance of success. The odds for success of African, coloured and Indian students are however lower than those of white students. The research indicated a decline of 8% in the number of successful students from 2007 to 2009, which pose a tough challenge for the institution, which could possibly be addressed by support programmes and providing financial support students that are not at risk as indicated in the study.